Self-triggering regime for synchronized formation of two droplets - Phan, Dinh-Tuan (2014)
This letter reports experimental results of the synchronized formation of two liquid droplets in a microfluidic device. A pair of droplets is formed periodically in a T-junction configuration with a single channel for the continuous phase and two inlets for the dispersed phase. The pair-wise droplet formation process is self-triggering, as the first droplet formed upstream triggers the breakup of the second droplet downstream. The triggered breakup happens across the different formation regimes. The effects of capillary number and flow rate ratio on the size and order of the droplets are investigated. The configuration reported here may serve as a parallel to serial sampling device for droplet-based lab-on-a-chip platforms.